The relation between sociodemographic factors and fatigue among urological nurses - Jarosz, Katarzyna; Młynarska, Agnieszka (Frontiers in Public Health, 2025)
BackgroundFatigue is a multifaceted and intricate condition resulting from high demands at work and within the healthcare system, as well as from personal factors and inadequate energy recovery. It can be triggered by a variety of predictors, including lifestyle choices, environmental conditions, and both physical and mental health issues. A particularly significant factor contributing to fatigue among nurses has been the COVID-19 pandemic, which has profoundly impacted their lives, work, and perspectives on their profession.PurposeThe aim of the study was to examine the fatigue levels among nurses working in urological wards and the sociodemographic factors related to them.MethodsThis is a cross-sectional study among 130 urological nurses. The questionnaire included the modified fatigue impact scale (MFIS) and metrics.ResultsIn our study, the mean fatigue rating was 52.68 (±16.06) points, and in the individual areas of the MFIS questionnaire, it was 24.10 (±7.34) points in physical functioning, 25.46 (±8.44) points in cognitive functions, and 5.76 (±2.13) points in psychosocial functions, suggesting that fatigue levels range between “sometimes” and “often” factors such as marital status, the number of illnesses among nurses, and the patient-to-nurse ratio are associated with the level of fatigue.ConclusionThere is a need to conduct more studies that will penetrate the fatigue experienced by nurses and the factors associated with it, especially the components related to marital status and health conditions among nurses. There is still a serious problem with nurse shortages, which cause fatigue and require more systemic solutions than just legal regulations.